PERANAN UREA PADA PENGOMPOSAN SERBUK GERGAJI JEUNGJING (ALBIZIA FALCATARIA) - Ridwan Achmad Pasaribu (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The composting experiment for the manufacture of compost from jeungjing sawdust has been done in the Forest Products Research and Development Centre, Bogor. The study reveals that a combination of 60 percent of jeungjing saw- dust and 40 percent of rice straw composted for about 35 days produced compost with 45,87 of C/N ratio which is in- ferior compare to the minimum C/N ratio of the soil that should be less than 20.In the past, attempts have been made by many workers to reduce C/N ratio of compost. Inclusion of additives such as urea in the composting, has been successfully done.The composting trials in the Forest Product Research and Development Centre was prepared by the mixture of 60 percent of jeungjing sawdust and 40 percent of rice straw, on which an amount of O; 3; 3,5; 5, 7 percent urea by weight was added to the mixture. The composting time were consecutively 8; 16; 24, and 32 days.This experiment reveals that :1.The analysis of variance of the C/N ratio content of the compost produced by different urea content and composting time, are significantly different.2.The composition of 60 percent jeungjing sawdust and 40 percent rice straw composted for about 35 days, produced compost with a relatively law C/N ratio (about 18,46). This is particularly true when 7,5 percent of the urea was engaged in the composting process. The C/N ratio content has met the requirement of the compost for fertilizer which is about 20.